Atypical Presentation of Cardiac Tamponade as a Cause of Acute Liver Injury: Case Report and Review of Literature - Thaker, Sarang (Cureus, 2018)
Pericardial tamponade is a rare cause of acute liver injury due to the compressive effects of an effusion resulting in a poor cardiac output which ultimately leads to ischemia-induced injury. We present a patient with chronic hepatitis C infection and end-stage renal disease who was transferred to our center for further evaluation and management of acute liver injury after presenting to an outside hospital with left upper quadrant abdominal pain, nausea and vomiting. The patient was discovered to have tamponade physiology on transthoracic echocardiogram as an underlying cause of his acute liver injury despite lack of clinical tamponade features. He required pericardiocentesis which eventually led to resolution of the acute liver injury and he was discharged home on day twelve after full recovery. We review the existing literature regarding the epidemiology, pathophysiology, clinical presentation, diagnosis, and treatment of ischemic hepatitis, which is associated with high mortality; therefore early recognition and treatment of the underlying cause are paramount.